Analisis Pengaruh Perkembangan Ekonomi Terhadap Nilai Penjualan Gas Tahun 2011-2022 Di Sumatera Utara : Penelitian - Claudia Tabitha Panjaitan; Monica Caramoy Sitorus; Olivia Damayanti Marpaung; Muammar El Zaidan; Bonaraja Purba (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the impact of gas sales on economic growth in North Sumatra Province during 2011–2022. Annual secondary data from the Central Statistics Agency (BPS) were analyzed using simple linear regression with the Ordinary Least Squares (OLS) method. The findings indicate a positive and significant effect of gas sales on Gross Regional Domestic Product (GRDP) at constant prices, with a coefficient of determination (R²) of 0.474. This suggests that nearly half of the variation in GRDP CP is explained by gas sales, while the remainder is influenced by other factors. The results underscore the critical role of the energy sector in fostering regional economic growth, consistent with previous studies highlighting its contribution to production and employment creation.